2017
DOI: 10.1007/978-3-319-72905-3_53
|View full text |Cite
|
Sign up to set email alerts
|

Study of Data Structures and Tools for the Concurrent Conceptual Design of Complex Space Systems

Abstract: Concurrent design facilities are used by space agencies and private organizations to conduct preliminary design activities in the development of space systems. Concurrent conceptual design is characterized by dynamic exchanges between a limited team of experts, defining the operational requirements, the systems architecture, the baseline design, and budgets for different resources. The results are a preliminary system baseline and product requirements that are used as inputs to the subsequent product developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The major differences are specialization on certain lifecycle phases and the focus and level of abstraction of parametric models. Fortin et al (2017) found out that only around 20% of the parameters in conceptual design describe geometry. Models used in the conceptual design of space systems primarily describe the system’s behavior; hence, tools deal little with geometry.…”
Section: A Collaboration Tool For Concurrent Conceptual Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The major differences are specialization on certain lifecycle phases and the focus and level of abstraction of parametric models. Fortin et al (2017) found out that only around 20% of the parameters in conceptual design describe geometry. Models used in the conceptual design of space systems primarily describe the system’s behavior; hence, tools deal little with geometry.…”
Section: A Collaboration Tool For Concurrent Conceptual Designmentioning
confidence: 99%
“…Such knowledge-based engineering approach is particularly advantageous when system designs can be generated based on models available for a product family (Prasad and Rogers, 2005). So far we did not include knowledge management capability into CEDESK, but we plan to add the possibility to store, search, and instantiate models from a component library as laid out in Fortin et al (2017).…”
Section: A Collaboration Tool For Concurrent Conceptual Designmentioning
confidence: 99%